ANALISIS PENYIMPANGAN PRAANGGAPAN DAN SKEMATA WACANA HUMOR PADA PENAMPILAN KOMEDI TUNGGAL RYAN ADRIANDHY - Fakhruzzahid, Muhammad (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to describe the deviation of prejudice, schemata, and the material context of Ryan Adriandhy's solo comedy performance. This study uses a pragmatic approach in describing the research data in linguistic units by referring to the theory of prejudice deviations (Yule, 2014), Piaget regarding schemata development, and discourse context (Hymes in Widodo). The data in this study are Ryan Adriandhy's speech on Stand-up comedy performances that contain preconceived deviations and schemata in seven different performances. The data in this study were obtained using the observation method and transcribed using the note-taking technique. In analyzing the data, the authors used qualitative data analysis procedures with the results presented in an informal explanation. The results of the research carried out were (1) the deviation of presuppositions found in Ryan Adriandhy's Stand-up comedy performance, namely: structural and general presupposition deviations, (2) schemata development that occurred in Ryan Adriandhy's Stand-up comedy performance, including two ways, namely: assimilation and accommodation, and (3) The discourse context contained in Ryan Adriandhy's stand-up comedy performance is divided into several constructions. It can be seen from the context of the show, the persona of the comic, and each item of the material.